Mechanical and physical properties of hybrid particleboard from bagasse and eucalyptus pellita / Muhammad Zikri Mohd Hashim - Mohd Hashim, Muhammad Zikri (Faculty of Applied Sciences, Universiti Teknologi MARA, Pahang, 2019)
Properties of particleboard from bagasse and Eucalyptus pellita in relation to fiber ratio and resin content bounded with urea formaldehyde has been studied. The particle board manufacturing was made with three fiber ratio 100% of bagasse, 50% bagasse mix with 50% Eucalyptus pellita and 100% of Eucalyptus pellita with 2 different percentage of resin content which is 10% and 14%. The boards produced were evaluated for its internal bonding (IB) testing, bending strength testing, thickness swelling (TS) and water absorption (WA) according to British Standard (EN312:1996). The measurement of internal bonding (IB), thickness swelling (TS) and water absorption (WA) IS 50mm x 50mm x 12mm while the measurement of bending strength (MOR and MOE) is 350mm x 50mm x 12mm.